البعد العسكري في الشّراكة الإستراتيجية بين روسيا و الصّين: جدلية التّعاون والتّنافس منذ نهاية الحرب الباردة . - بركاني, سليم (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
لقد عرفت العلاقات بين موسكو و بكين، بعد الحرب الباردة، تقاربا معتبرا أدّى إلى قيام " الشّراكة الإستراتيجية بين روسيا و الصّين ". و في هذا المقال، سنتناول البعد العسكري من هذه الشّراكة الإستراتيجية في ضوء الإشكالية التّالية: هل ستؤدي العلاقات العسكرية بين روسيا و الصّين إلى قيام تحالف بين البلدين ؟. و لتحقيق ذلك منهجيا: حددنا السّياقات الدّاخلية و الخارجية لعلاقاتهما العسكرية ؛ ثم قمنا باستعراض مظاهر التّعاون و التّنافس العسكري بينهما و تبيان دلالاتهما المختلفة ؛ و أخيرا، قدمنا رؤية عن الآفاق المستقبلية للعلاقات العسكرية الرّوسية - الصّينية. و قد توصلنا إلى أن توافق المصالح بين روسيا و الصّين يؤدي إلى تعاونهما و أنّ العكس صحيح ؛ و أنّ هذه العلاقات لا تتحول إلى تحالف بينهما على المدى المنظور. Abstract: Following the end of the cold war, there has been a significant rapprochement between MOSCOW And PEKIN marked by the establishment of the « Strategic Partnership Between Russia And China » ; in which, their military relations witnessed a great development. In this article, we will discuss the military dimension of this strategic partnership with the following problematic: Will military relations between RUSSIA and CHINA lead to an ALLIANCE between them?. methodologically, first: we identified the internal and external contexts of their military relations ; Then, we reviewed their manifestations ; and then, we indicated their various significances ; next, we presented a vision of their future prospects ; finallaly, we have concluded that the convergence of interests between RUSSIA and CHINA leads them to military cooperation, and that the opposite is true ; and their actually relations don’t permit the establishment of an ALLIANCE between them.